2001
DOI: 10.1161/hh2301.100982
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cardiac Sympathetic Activity and Insulin-Like Growth Factor-I Formation Are Associated With Physiological Hypertrophy in Athletes

Abstract: Abstract-Physiological hypertrophy represents the adaptive changes of the heart required for supporting the increased hemodynamic load in regularly trained healthy subjects. Mechanisms responsible for the athlete's hypertrophy still remain unknown. In 15 trained competitive soccer players and in 15 healthy men not engaged in sporting activities (sedentary control subjects) of equivalent age, we investigated the relationship among cardiac growth factor formation, cardiac sympathetic activity, and left ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(136 citation statements)
references
References 56 publications
3
122
0
5
Order By: Relevance
“…Further remodeling in response to long‐term exercise training involves the expression of cytokines and growth factors (eg, vascular endothelial growth factor A, transforming growth factor ß, platelet‐derived growth factor, fibroblast growth factors 1 and 2, and insulin‐like growth factor), which leads to the proliferation and growth of endothelial cells and smooth muscle cells and ultimately drives the arteriolarization of capillaries2, 43, 44, 45, 46 (Figure 2). In the trained heart, the consequence is unaltered capillary density, but there is a larger and more profound arterial supply 2, 47.…”
Section: Adaptation Of Coronary Circulation To Exercise Training In Tmentioning
confidence: 99%
“…Further remodeling in response to long‐term exercise training involves the expression of cytokines and growth factors (eg, vascular endothelial growth factor A, transforming growth factor ß, platelet‐derived growth factor, fibroblast growth factors 1 and 2, and insulin‐like growth factor), which leads to the proliferation and growth of endothelial cells and smooth muscle cells and ultimately drives the arteriolarization of capillaries2, 43, 44, 45, 46 (Figure 2). In the trained heart, the consequence is unaltered capillary density, but there is a larger and more profound arterial supply 2, 47.…”
Section: Adaptation Of Coronary Circulation To Exercise Training In Tmentioning
confidence: 99%
“…Also, swimming mediated induction of αMHC expression was found to be blocked by sympathectomy or pretreatment of animals with β-adrenergic receptor blockers [64,65,97,100]. Recent studies carried out on human athletes and swimmers have also demonstrated increased cardiac sympathetic activity and formation of IGF1, associated with physiologic hypertrophy [64,101,102]. These studies together have strengthened the notion of enhanced adrenergic receptor activity for the induction of αMHC expression during physiologic hypertrophy.…”
Section: Cardiac Hypertrophymentioning
confidence: 99%
“…cardiac loading conditions [3,33]. These compensatory mechanisms are beneficial during stress and acute changes in the circulatory system [24,29,30,45].…”
Section: Discussionmentioning
confidence: 99%